REDUCING THE LIKELIHOOD OF ELECTRICAL POWER-RELATED DISASTERS: A FUZZY MCDM APPROACH - Setiawan, Eko; Astuti, Septin Puji; Handoko, Handoko (Simetris: Jurnal Teknik Mesin, Elektro dan Ilmu Komputer, 2018)
Many of disasters are related to electrical power systems. They affect human life and economy. In order to reduce the negative impacts caused by the failure of electricity power system due to disasters and to create a robust electrical power system, selecting the best relay of electricity power is a must. This study identified the best protective relay of electrical power systems of PLN in Surakarta region by applying analytic hierarchy process (AHP), one of MCDM approaches, combined with fuzzy logic. Extent analysis approach was implemented to derive priorities of various criteria, sub-criteria and alternatives. Three relays being considered in the selection process are electromagnetic relay, digital relay and static relay. Four criteria in this study are techno-economy, fault frequency, protection of transmission line and advantage of relay over others. Meanwhile, five sub-criteria for each criterion are reliability, selectivity, sensitivity, working speed and efficient. Based on the criteria and sub-criteria, it can be inferred that in terms of four working areas of PLN management in Surakarta region, digital relay is seen as the best choice of relays.